Gamma-secretase modulators: a promising route for the treatment of Alzheimer's disease - Nordvall, Gunnar; Lundkvist, Johan; Sandin, Johan (Frontiers in Molecular Neuroscience, 2023)
Recent clinical data with three therapeutic anti-Aβ antibodies have demonstrated that removal of Aβ-amyloid plaques in early Alzheimer's disease (AD) can attenuate disease progression. This ground-breaking progress in AD medicine has validated both the amyloid cascade hypothesis and Aβ-amyloid as therapeutic targets. These results also strongly support therapeutic approaches that aim to reduce the production of amyloidogenic Aβ to prevent the formation of Aβ-pathology. One such strategy, so-called gamma-secretase modulators (GSM), has been thoroughly explored in preclinical settings but has yet to be fully tested in clinical trials. Recent scientific progress has shed new light on the role of Aβ in Alzheimer's disease and suggests that GSMs exhibit specific pharmacological features that hold great promise for the prevention and treatment of Alzheimer's disease. In this short review, we discuss the data that support why it is important to continue to progress in this class of compounds.